A taste for brown sugar : black women in pornography - Miller-Young, Mireille, 1976- (Duke University Press, 2014)
Based on extensive archival and ethnographic research on dozens of women who have worked in adult entertainment since the 1980s, A Taste for Brown Sugar boldly takes on representations of black women's sexuality in the porn industry.